Analyzing the relationship between stock market volatility and economic activity in the USA - المعموري, محمد علي موسى; فتح الله, سحر; احمد, حيدر حسين (Journal of Economics and Administrative Sciences, 2011)
This study examines the dynamic relationship between stock market and economic activity in the United States to verify the possibility of using financial indicators to monitor the turning points in the expected path of future economic activity. Has been used methodology (Johansen - Juselius) for the Co-integration and causal (Granger) to test the relationship between the (S & P 500 , DJ) index  and gross domestic product (GDP) in the United States for the period (1960-2009). The results of the analysis revealed the existence of a causal relationship duplex (two-way) between the variables mentioned. which means the possibility of the use stock market indicators to predict of fluctuations in economic activity.